Clothing and Teacher Credibility: An Application of Expectancy Violations Theory. (29th February 2012) - Dunbar, Norah E.; Segrin, Chris
Abstract : Clothing is an important aspect of communication that can influence the perceptions of wearers' credibility and attractiveness as well as a variety of other judgments. In the classroom, these perceptions are made by students about teachers and are a function of the type of behavior expected from their teachers. This paper argues that we have expectations for appropriate and inappropriate attire. Burgoon's expectancy violations theory was applied to the study of clothing and the credibility of instructors in college classes. Two instructors gave lectures in undergraduate college classes and violated or adhered to the students' expectations for appropriate attire and acted in a highly rewarding or less rewarding manner. The results do not support the U-shaped pattern predicted by expectancy violations theory, but rather, the results suggest that teachers should strive for a moderately formal clothing style. This result is qualified by the finding that students appeared to have attended to their instructors' clothing less under conditions of high reward than in the low-reward conditions. This suggests that teachers' clothing will be a less consequential determinant of the impression that their students form when the teachers are otherwise perceived as having a high instrumental value in and of themselves.